COVID-19 vaccine acceptance among pregnant women attending antenatal care in public hospitals in eastern Ethiopia: A multi‐center facility‐based cross‐sectional study - Tamirat Getachew; Bikila Balis; Addis Eyeberu; Adera Debella; Shambel Nigussie; Sisay Habte; Bajrond Eshetu; Habtamu Bekele; Addisu Alemu; Yadeta Dessie (Elsevier, 2022)
Objectives: The Ethiopian government had planned to vaccinate the total population and started to deliver the COVID-19 vaccine but, there is limited evidence about vaccine acceptance among pregnant women. Thus, this study aimed to assess COVID-19 vaccine acceptance and associated factors among pregnant women attending an antenatal care unit clinic in Eastern Ethiopia. Study design: A facility-based cross-sectional study. Methods: A study was conducted from June 01 to 30/2021 among systematically selected pregnant women. Data were collected using a pre-tested structured questionnaire, which was adapted from previous studies, through a face-to-face interview. Predictors were assessed using a multivariable logistic regression model and reported using an adjusted odds ratio with 95% CI. Statistical significance was declared at p-value less than 0.05. Results: In this study, data from 645 pregnant women were used in the analysis. Overall, 62.2% of pregnant women were willing to be vaccinated if the vaccine is approved by the relevant authority. Fear of side effects (62.04%), a lack of information (54.29%), and uncertainty about the vaccine's safety and efficacy (25%) were the most common reasons for refusal to take the COVID-19 vaccine. The odds of unwillingness to accept the COVID-19 vaccine among pregnant women were increased significantly among mothers who were able to read and write [AOR = 2.9, 95% CI: (1.16, 7.23)], attain 9-12 grade level [AOR = 4.2, 95% CI: (2.1, 8.5)], lack information [AOR = 2.2, 95% CI: (1.41, 3.57)], and having a history of chronic diseases [AOR = 2.52, 95% CI: (1.34, 4.7)]. Conclusion: Less than two-thirds of pregnant women were willing to accept the COVID-19 vaccine. Extensive public health information dissemination aimed at women with lower educational backgrounds and a history of chronic disease could be critical.